Polacy czy obywatele? Lud w programach polskich partii politycznych (2001-2023) (Politeja, 2025)
POLES OR CITIZENS? „PEOPLE” IN POLISH POLITICAL PARTIES’ MANIFESTOS (2001-2023)This article examines the extent to which Polish political parties refer to “the people” in their manifestos. The analysis categorizes references to “the people” into six types: geographical (Poles, nation), legal (citizens), political (voters), economic (working people), moral (those who share similar values, religions, or worldviews), and general (people, everyone). It then determines what proportion of each party’s manifesto consists of such references. This study proposes a novel quantitative approach to the analysis of “the people” in party programs, aiming to identify whether systematic patterns or correlations exist. The analysis also identifies patterns such as emphasizing the people’s virtues, portraying them as a homogeneous group, or calling for their sovereignty – features that may indicate a party’s populist orientation. The research addresses which groups parties refer to and to what extent these references vary depending on time, parliamentary status (government vs. opposition), systemic presence (parliamentary vs. non-parliamentary), economic orientation, and position on the GAL-TAN axis.